Andrographolide Reverses Doxorubicin Resistance in Human Breast Cancer Stem Cells by Regulating Apoptotic Gene Expressions - Septelia Inawati Wanandi; Resda Akhra Syahrani; Ayu Suraduhita; Elvira Yunita; Melva Louisa (The Indonesian Biomedical Journal, 2023)
BACKGROUND: Breast cancer stem cells (BCSCs) have been identified as playing a crucial role in therapeutic resistance. This resistance can be attributed to the anti-apoptotic protein survivin and the antioxidant MnSOD high expression. To overcome the resistance to doxorubicin (DOX), this study proposed the utilization of andrographolide (ANDRO), the primary bioactive compound in Andrographis paniculata leaves. The objective was to examine the role of andrographolide in regulating survivin, caspase-9, and caspase-3 gene expressions to reverse doxorubicin resistance in human BCSCs.METHODS: BCSCs were exposed to 0.1 µM DOX every two days or 50 µM rotenone (ROT) for 6 hours, subsequently supplemented with 0.3 mM ANDRO. Superoxide and peroxide levels were measured using DHE and DCFH-DA assay. The MnSOD, survivin, caspase-9, and caspase-3 mRNA expression levels were analyzed using qRT-PCR. Protein expressions were evaluated using Western blotting assay. MnSOD activity was determined using xanthine oxidase inhibition assay. The apoptotic cells were determined using Annexin-V/PI staining.RESULTS: This study indicated that the cytotoxic mechanisms of DOX, similar to ROT, in BCSCs were attributed to oxidative stress, as evidenced by an elevation in superoxide rather than peroxide levels, accompanied by a decrease in MnSOD activity. This study also highlighted that ANDRO reversed DOX resistance in BCSCs subjected to repeated DOX treatment by downregulating survivin and upregulating caspase-9 and caspase-3 mRNA expressions, thereby activating the intrinsic apoptotic pathway.CONCLUSION: This study provides insights into the role of ANDRO in modulating the expression of apoptotic genes, such as survivin, caspase-9, and caspase-3, to overcome DOX resistance in BCSCs.KEYWORDS: breast cancer, breast cancer stem cell, andrographolide, doxorubicin, oxidative stress, apoptosis